Effect of Ethanol Extracts of Musa paradisiaca Fruit Pulp and Peels on Haematological Indices and Liver Enzymes of Experimental Rats - Emuesiri Goodies Moke; Emuesiri Kohworho Umukoro; Evelyn Tarela Ojugbeli; Theresa Ezedom; Tarela Melish Elias Daubry; Iziegbe Lisa Omorodion (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
Medicinal plants usage in traditional medicine has risen over the years. Musa paradisiaca has been reported that it possesses various therapeutic efficacies. This study is aimed at evaluating the effect of parts of the ethanol fruit extracts of Musa paradisiaca on haematological indices and serum liver enzymes. Thirty Wistar rats were grouped into five groups of six animals each which were administered 200 mg/kg and 400 mg/kg of Musa paradisiac fruit (MPF) pulp extract or peel extract. Haematological indices and liver enzymes were assayed for at the end of the 14-days experimental period. MPF pulp and MPF peel at 400 mg/kg showed a significant (P<0.05) increase in red cell count and haematocrit level as compared to the control. There was a non-significant (P>0.05) increase in haemoglobin concentration in the treated rats as compared to the control. There was also a non-significant (P>0.05) change in AST, ALT, and ALP level of the treated rats as compared to the control. Fruit pulp and peel of Musa paradisiaca improve erythrocytes count and haematocrit level, and they may not be associated with liver toxicity.